Magnet Ingestions in Children Presenting to Emergency Departments in the United States 2009–2019: A Problem in Flux. Issue 6 (December 2020) - Reeves, Patrick T.; Rudolph, Bryan; Nylund, Cade M.
ABSTRACT: Objectives: Small rare-earth magnet (SREM) ingestions are a dangerous, potentially fatal health hazard in children. The U.S. Consumer Safety Commission removed these products from the market in 2012 until a federal court decision vacated this action in 2016. The present study aims to investigate whether the reintroduction of SREMs is associated with an increase in the national frequency of magnet ingestions in children. Patients and Methods: Data from the National Electronic Injury Surveillance System (NEISS) were used to evaluate suspected magnet ingestion (SMI) trends within patients (0–17 years) from 2009 to 2019. SMI cases were stratified (total, small/round, and multiple magnet ingestions) and trend analyses were performed for 2 periods: 2013–2016 (off-market) and 2017–2019 (on-market). National SMI estimates calculated using the NEISS-supplied weights and variance variables. Results: An estimated 23, 756 children (59% males, 42% < 5 years old) presented with a SMI from 2009 to 2019 with an average annual case increase of 6.1% ( P = 0.01). There was a significant increase in both small/round SMI encounters and multiple magnet ingestion encounters from 2009 to 2019 ( P < 0.001 and P < 0.01, respectively). From 2017 to 2019, there was a greater proportion of small/round type SMIs to total SMIs estimated n = 541 (confidence interval [CI], 261–822) and a greater proportion of multiple magnet ingestions to total SMIs estimated n = 797 (CI, 442–1152) (both, P < 0.01). After 2017, there was a 5-fold increase in the escalation of care for multiple magnet ingestions (estimated n = 1094; CI 505–1686). Conclusions: The significant increase in magnet ingestions by children from 2017 to 2019 indicates that regulatory actions are urgently needed to protect children and reverse these trends. Abstract : Supplemental Digital Content is available in the text